Familial dyslexia and sound duration in the quantity distinctions of Finnish infants and adults - Richardson, Ulla (1998)
This study investigates the role of duration in the categorisation of speech sounds into prosodically distinct phonemes by dyslexic adults and their infants, in the Finnish context. The duration of sounds has a significant role in Finnish quantity distinctions and the quantity aspect is visibly marked in the Finnish orthography. Previous research has shown controversial evidence on the temporal processing abilities of dyslexics. In the infant perception experiment a head-tum paradigm was used to test 6-month old infants' perception of speech stimuli in which the duration of a stop was varied. There were 89 subjects, half of whom were infants with high genetic risk for dyslexia (GR+) while the other half were controls (GR-). The results indicated that the GR+ infants require significantly longer duration than the GR- infants to shift their perception from the short to the long quantity category. The same experiment adapted for adults showed that also adult dyslexics may have a deficiency in processing temporal information. The same adults and infant subjects took part in production experiments. The results showed that the GR+ infants differed from the adults more than GR- infants in using durational cues for (C)VCV and (C)VCCV structures. In particular, the secondary cue in these word structures appeared to be troublesome for the GR+ infants. Also the dyslexic adults differed from the control adults in the use of the secondary cue in CVCV structures. The findings suggest that there may be a basic temporal processing deficiency in dyslexics which is apparent early in their development.